EVALUASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT PESISIR - HENDRIKS, DELIN; PARERA, AMLIA; DOMINGGUS, DOMINGGUS; UBUWAL, FERONIKA LIDIA; AITOMAS, RIVAT (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This research aims to evaluate the effectiveness of Corporate Social Responsibility (CSR) programs in improving coastal community welfare through a systematic literature review approach. The research method involves analyzing 50 scientific articles published between 2013-2024, focusing on the implementation and impact of CSR programs in coastal areas. The results show a paradigm shift from charity-based approaches to community development, with program success rates reaching 65%. CSR programs successfully increased community income by 35-45%, strengthened local institutions in 30 cases, and integrated environmental conservation in 20 programs. Key success factors include community participation (85%), government support (75%), thorough planning (70%), and sustainable assistance (65%). This research recommends developing comprehensive evaluation models, strengthening local institutions, and integrating programs with regional development policies to enhance the effectiveness and sustainability of CSR programs in coastal areas.